2018
DOI: 10.1021/acs.jafc.8b00834
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of β-Lactoglobulin-Based Nanocomplexes Composed of Chitosan Oligosaccharides as Vehicles for Delivery of Astaxanthin

Abstract: Astaxanthin (Ax), a type of carotenoid, has limited use as a result of its poor water solubility, low bioavailability, and decomposition under harsh conditions. This study reports a delivery system for Ax through a simple affinity binding with β-lactoglobulin and then coated with chitosan oligosaccharides. Ax-loaded β-lactoglobulin nanocomplexes and chitosan oligosaccharide-coated nanocomplexes were successfully prepared. The nanocomplexes exhibited a smooth spherical shape with diameters of about 40 and 60 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 29 publications
2
35
0
Order By: Relevance
“…The method for evaluating the stability of FX and FX@PVP NPs was slightly modified according to Tie et al [38] and Liu et al [39]. The thermal stability was assessed by placing equal volumes (1 mL) of samples in a water bath at different temperatures (40, 50, 60 • C) for 24 h, then the contents of FX in freeze-dried samples were determined by HPLC.…”
Section: Stability Of Fx@pvp Npsmentioning
confidence: 99%
“…The method for evaluating the stability of FX and FX@PVP NPs was slightly modified according to Tie et al [38] and Liu et al [39]. The thermal stability was assessed by placing equal volumes (1 mL) of samples in a water bath at different temperatures (40, 50, 60 • C) for 24 h, then the contents of FX in freeze-dried samples were determined by HPLC.…”
Section: Stability Of Fx@pvp Npsmentioning
confidence: 99%
“…Given these conditions, some researchers developed effective strategies such as nanoparticulate drug delivery technologies to overcome these problems and enhance the bioavailability of astaxanthin. For example, Liu et al developed a new delivery system, which encapsulated astaxanthin with β-lactoglobulin and chitosan oligosaccharides to improve the stability and antioxidant activity of astaxanthin [11], and Wu et al . reported that astaxanthin was successfully incorporated into hyaluronic acid nanoparticles via an electrostatic field system and had a better recovery effect than astaxanthin alone on retrorsine–CCl 4 -induced liver fibrosis in the rat model [12].…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, whey proteins concentrate (WPC), a generally recognized as safe (GRAS) material with high nutritional value, has been employed as a carrier to produce water-dispersible ASX nanoparticles (NPs). WPC represents an added-value byproduct of the cheese production chain and a cheaper solution in comparison to recently described solutions based on purified whey proteins [25]. The incorporation of carotenoids in a nanocarrier also poses relevant stability issues.…”
Section: Introductionmentioning
confidence: 99%